Parents’ Assistance in Anti-retroviral Therapy Adherence of HIV/AIDS Adult Child - Kespichayawattana, Jiraporn; Wivatvanit, Suvinee; Saengtienchai, Chanpen (Journal of Health Science of Thailand, 2018)
The expanding of universal access to affordable anti-retroviral therapy (ART) for HIV infected persons by the Thai government, resulted in the success of decreasing mortality of HIV/AIDS cases. This study was aimed at examining the roles of family members, especially parents involving in assisting ART adherence of the adult children. Data were collected, by using self-administered questionnaires, from 912 adult ART recipients who attended services at out-patient clinics for HIV/ AIDS or anonymous clinics at community hospitals or provincial hospitals in six provinces. Results indicated that the large majority (83%) of ART patients reported having at least one parent alive and more than half of these (60%) lived with or in the same locality as a parent. Patients accessing ART under the universal coverage scheme were generally required to obtain their supply at the nearest hospital–mainly community hospitals. Spouse and parents were family members who commonly assisted ART patients in taking their medications. Moreover, parents often reminded adult sons and daughters to go for re-supplies and sometimes brought or accompanied them to clinics. The results underscore the need to incorporate close family members, including parents, more explicitly into programs intended to augment ART adherence and to facilitate their effectiveness which health personnel should not overlook.